2020
DOI: 10.3390/cancers12061446
|View full text |Cite
|
Sign up to set email alerts
|

Rlip Depletion Suppresses Growth of Breast Cancer

Abstract: RLIP76 (RAL-binding protein-1, Rlip) is a stress-protective mercapturic-acid-pathway transporter protein that also plays a key role in regulating clathrin-dependent endocytosis as a Ral effector. Targeted inhibition or depletion of Rlip causes regression of xenografts of many cancers and is capable of abrogating tumor formation in p53-null mice. This is associated with the reversion of the abnormal methylomic profile of p53-null mice to wild-type. In a query of The Cancer Genome Atlas (TCGA) databases, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 74 publications
2
24
0
Order By: Relevance
“…Rlip-LNA and LNA control antisense (CAS) were purchased from Exiqon (Woburn, MA, USA). Sources of reagents for qRT-PCR, western blot, and genotyping were the same as previously described [62][63][64]. All reagents were of analytical grade.…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rlip-LNA and LNA control antisense (CAS) were purchased from Exiqon (Woburn, MA, USA). Sources of reagents for qRT-PCR, western blot, and genotyping were the same as previously described [62][63][64]. All reagents were of analytical grade.…”
Section: Reagentsmentioning
confidence: 99%
“…Lungs were removed, air-evacuated, and fixed in 10% buffered formalin phosphate before automated paraffin embedding for metastasis quantification. Tumor tissues were cut into ∼5 mm thick slabs followed by H&E staining of embedded tissue by the Pathology Core Facility at TTUHSC [62]. The number of pulmonary metastases was counted under a camera-equipped stereomicroscope.…”
Section: Tumor Growth and Tissue Processingmentioning
confidence: 99%
“…Concomitant deficiencies of GS-E efflux, GSH-linked antioxidant defenses and CDE-linked vesicular trafficking in RALBP1-null (RALBP1 −/− ) mice show that RALBP1 functions provide an essential link between stress-induced apoptosis defenses and RAL/RAS/RHO/RAC-regulated pathways that promote cancer cell growth [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Our recent studies in lung and breast cancers as well as melanoma have confirmed that the inhibition or depletion of RALBP1 blocks CDE and inhibits signaling by cancer-promoting peptides, including EGF, WNT and FGF [ 10 , 11 , 13 , 14 ]. The role of RALBP1 in regulating intracellular vesicular traffic, and the signaling proteins, such as ARF6, ARNO, PI3K and RAC, that regulate vesicular traffic, is reviewed in one paper presented in this symposium issue.…”
mentioning
confidence: 97%
“…In stark contrast, mice lacking the RALBP1 ((RalA Binding Protein 1) gene, which encodes RLIP76 (also known as Rlip (RALBP1), used here for both gene and protein), a stress-responsive, anti-apoptotic protein, are highly resistant to carcinogenesis by even the most potent chemical carcinogens [ 10 ]. Targeted inhibition or depletion of RALBP1 causes regression of many types of cancer [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. In studies to examine the effect of combined RALBP1 and TP53 deficiency, we discovered that hemizygous RALBP1 deficiency was sufficient to exert a strong dominant negative effect on the spontaneous carcinogenesis phenotype of homozygous TP53-null mice [ 10 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation